Analysis of Phonetic Errors in Learning Arabic Through Social Media Tiktok - Dewi, Azzaria Mida Mustika; Musthofa, Tulus; Rauf, Abdul (STUDI ARAB, 2023)
Learning to use social media is no stranger in this digital era. One of the social media that is the choice as a learning medium is Tiktok. Its many users from all circles, which is the reason that Tiktok social media can be used to achieve learning goals. It can be seen from Arabic language learning that can be carried out through Tiktok social media. The purpose of this study is to define and classify Arabic pronunciation errors and provide suggestions so that these phonetic errors are not sustainable. This research method uses a descriptive qualitative approach. Research data analysis techniques are watching, listening, and taking notes. The results of this study are that there are more phonetic errors in learning Arabic through the social media Tiktok in Arabic writing, whereas in Arabic speaking it is still relatively minimal.